2020
DOI: 10.3390/ijerph17145098
|View full text |Cite
|
Sign up to set email alerts
|

On the Way to the Marathon—Motivation for Participating in Mass Running Events Among Children and Adolescents: Results of the Poznan Half Marathon Pilot Study

Abstract: The market for mass sports events geared towards adults is already saturated, while more new initiatives are exclusively targeting children and adolescents. Mass sports events for amateur athletes can be a great way to encourage young people to exercise regularly, such as in cases where physical education classes do not fully play this role. A lot of research has already been conducted on the subject of adult motivation for participating in amateur sports events, i.e., marathons, ultramarathons, duathlons or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…These motives categories have been used previously in research with adult runners during COVID-19 (DeJong et al, 2021 ). While other questionnaires on running motivation exist [e.g., Motivation of Marathoners Scale (Zach et al, 2017 )], we agreed with other authors on its validity in a youth population (Malchrowicz-Mosko et al, 2020 ) who were non-marathoners. Runners were also asked about their most common running companion(s) [“by myself,” “with my family member(s),” “with my friend(s),” “with my teammate(s),” “with my coach(es)”].…”
Section: Methodssupporting
confidence: 87%
“…These motives categories have been used previously in research with adult runners during COVID-19 (DeJong et al, 2021 ). While other questionnaires on running motivation exist [e.g., Motivation of Marathoners Scale (Zach et al, 2017 )], we agreed with other authors on its validity in a youth population (Malchrowicz-Mosko et al, 2020 ) who were non-marathoners. Runners were also asked about their most common running companion(s) [“by myself,” “with my family member(s),” “with my friend(s),” “with my teammate(s),” “with my coach(es)”].…”
Section: Methodssupporting
confidence: 87%
“…Respondents rated the aspect of making friends thanks to martial arts training very high. By contrast, aspects of affiliation were not important for young runners [38]. Our study showed that adolescents gave the intrinsic motivation to experience stimulation and the intrinsic motivation to accomplish the highest ratings.…”
Section: Discussioncontrasting
confidence: 59%
“…In the future, more characteristics of inexperienced runners should be investigated, such as agerelated motivations by gender, athletes' health status, or the number of children in the family. Moverover, in the future beginner children should be checked and add our reference about children (53).…”
Section: Discussionmentioning
confidence: 99%